Approximation of Smooth Stable Invariant Manifolds for Stochastic Partial Differential Equations (Journal of Partial Differential Equations, 2019)
Invariant manifolds are complicate random sets useful for describing andunderstanding the qualitative behavior of nonlinear dynamical systems. The purposeof the present paper is try to approximate smooth stable invariant manifolds for atype of stochastic partial differential equations with multiplicative white noise nearthe fixed point. Two examples are given to illustrate our results.
Keywords: Stochastic partial differential equation; smooth stable invariant manifold; geometric shape; analytical approximation.